The relationships between social support and three forms of sexism: can social support alleviate the effects of sexism? - Chu, Po Sen (Kansas State University, 2011)
Research on contemporary sexism suggests that sexism has many different forms and they influence women differently. Evidence shows that women who experience subtle forms of sexism (e.g., modern and benevolent sexism) feel anxious and less competent, yet are less likely to identify these forms of sexism as prejudice against women. Because research suggests that social support is related to better psychological outcomes, we hypothesized that higher levels of perceived social support would be associated with better psychological outcomes among female participants who experienced sexism. In addition, receiving a supportive message after experiencing sexism would buffer the negative psychological effects of sexism, and thus the participants would perform better on a problem-solving task. However, the results only partially supported the hypotheses. Higher levels of perceived social support were indeed associated with better psychological outcomes, but participants who experienced sexism did not differ significantly from those who did not experience sexism regarding psychological outcomes. Further, receiving social support after experiencing sexism did not produce significant improvements on the problem-solving task, though participants who experienced modern sexism did report an increase in hostile affect if they did not receive social support. Possible reasons for the findings are discussed.
Keywords: sexism; social support; Psychology (0621)